(untitled) (Baghdad Science Journal, 2021)
The applications of hot plasma are many and numerous applications require high values of the temperature of the electrons within the plasma region. Improving electron temperature values is one of the important processes for using this specification in plasma for being adopted in several modern applications such as nuclear fusion, plating operations and in industrial applications. In this work, theoretical computations were performed to enhance electron temperature under dense homogeneous plasma. The effect of power and duration time of pulsed Nd:YAG laser was studied on the heating of plasmas by inverse bremsstrahlung for several values for the electron density ratio. There results for these calculations showed that the effect of increasing the values of the laser pulse power (25-250kW) led to decrease the absorption coefficient values by 58.3% and increase the electron temperature by 50.0% at duration pulse time 0.5ns and electron density ratio 0.1. Furthermore, the ratio of electron density increasing and pulse duration time led to increase the higher values of the electron temperature. The results of the calculations showed the effect of the laser power, the percentage of electron density, and the pulse duration for improving the electron temperature. It is possible to control the temperature of the electrons with one of the plasma parameters or the laser beam used, and that it gives a clear indication of researchers in this field to choose the optimal wavelength of the laser beam and electron density ratios for the plasma.